PRECONCEPTION AND PRENATAL DIAGNOSTIC TECHNIQUES ACT 1994 AND ITS MAIN ROLE TO CURB SEX DETERMINATION AND SEX SELECTION - Waghmare, Vaishali; Hema, Hema (International Journal of Research -GRANTHAALAYAH, 2016)
India has a male dominated culture where women are treated like a commodity and slave. Our Indian society gives preference only to the Son not to female because of which girls’ child is not heartily welcomed and discrimination against girl child still prevails. Sex selective abortion is one of major issue in recent era in relation to violence against women under which the Ultrasonography machine plays an important role of sex detection. Main cause for sex selection are Patriarchal system, Dowry system, only son who can performs the last rites, lineage and inheritance runs through the male line, the Small family norms , PARAYADHAN, easy access to the Medical facilities and Technology for Sex Selective Abortion. Low literacy rate, low socio-economic condition of women etc. Sex selection and sex determination causes violence, impact on equilibrium of nature, Polyandry, Imbalance between Male-Female populations etc Maharashtra was first State to enact Maharashtra regulation of use of PNDT Act in 1987. The PNDT Act was passed in 1994 Hon. Supreme Court passed an Interim judgment in 2001 for more strict implementation of Act based on PIL filed by CEHAT, MASUM and AdvSabu George PNDT Act amended in 2003 to Pre conception and Pre-natal Diagnostic Technique Act (PC-PNDT) Applicable to all Govt/NGO/Private/corporate establishments . Main purpose of Act is to ban the use of sex selection techniques before and after conception and prevent the misuse of prenatal diagnostic techniques for sex selective abortion. Every offence under this Act is cognizable, non-bailable and non-compoundable (Sec 27). Act has made it mandatory to maintain records of every scan done. (Section 29 and Rule 9) Section 5 and Rule 10 (1A).Implementing Authority under the Act is Appropriate Authority (Section 17) has power to search, seize and seal clinics (Section 30). The Act prohibited communication of sex of the foetus by words, signs or in any other manner (Section 5) , advertising sex determination test in any form are liable for punishment (Section 22) .Offence under this Act punishable with imprisonment of years which extend to 5 years and fine up to 10,000 which extend up to 50,000.